Endoplasmic reticulum protein targeting of phospholamban: a common role for an N-terminal di-arginine motif in ER retention? - Parveen Sharma; Vladimir Ignatchenko; Kevin Grace; Claudia Ursprung; Thomas Kislinger; Anthony O Gramolini (PLoS ONE)
Background Phospholamban (PLN) is an effective inhibitor of the sarco(endo)plasmic reticulum Ca(2+)-ATPase, which transports Ca(2+) into the SR lumen, leading to muscle relaxation. A mutation of PLN in which one of the di-arginine residues at positions 13 and 14 was deleted led to a severe, early onset dilated cardiomyopathy. Here we were interested in determining the cellular mechanisms involved in this disease-causing mutation. Methodology/principal finding Mutations deleting codons for either or both Arg13 or Arg14 resulted in the mislocalization of PLN from the ER. Our data show that PLN is recycled via the retrograde Golgi to ER membrane traffic pathway involving COP-I vesicles, since co-immunoprecipitation assays determined that COP I interactions are dependent on an intact di-arginine motif as PLN RDelta14 did not co-precipitate with COP I containing vesicles. Bioinformatic analysis determined that the di-arginine motif is present in the first 25 residues in a large number of all ER/SR Gene Ontology (GO) annotated proteins. Mutations in the di-arginine motif of the Sigma 1-type opioid receptor, the beta-subunit of the signal recognition particle receptor, and Sterol-O-acyltransferase, three proteins identified in our bioinformatic screen also caused mislocalization of these known ER-resident proteins. Conclusion We conclude that PLN is enriched in the ER due to COP I-mediated transport that is dependent on its intact di-arginine motif and that the N-terminal di-arginine motif may act as a general ER retrieval sequence.